EFEKTIVITAS E-GOVERNMENT DI KEJAKSAAN TINGGI ACEH JAYA - Muis, Muis; Risdan, Risdan; Zulfikar, Zulfikar (Universitas Jabal Ghafur, 2022)
Thisaresearchacanabeasaid to be importantabecause the developmentiof informationiand communicationttechnology haagiven birth to theaeffectiveness of E-Government. By using informationitechnology in accordancelwith the needs 0f the oorganizatin, it will berable to managebdata quickly, effectivelydand efficientlydandproduce precise,hfast, and accurate information.hHowever, the implementation is stillafar fromeexpectations, withethis researchi it is hopedathat the answeriwill be answered.aThe formulation of theaproblem in th!s thes!s is how the effectiveness of E-Government in the Aceh Jaya High Court is. How is the use of informatlon technolgyi appIied at the Aceh JayaaHigh Prosecutor'siOffice in processingilegal administration.BThis study usespqualitative methods,wdata collectionpthroughdobservation, interviews,ddocumentation. The informants consisted of the Head of the High Court, several related assistants and several communities who submitted cases to be handled by the prosecutor's office in settlement. The technique of checking the validity of the data using the criteria of empathy. The results showed that E-Government at the Aceh Jaya HighpCourt in utilizingoinformation technologydto achieveswork resultslefficiently washabIe to manageldata quickly,peffectively and efficientlypand producenprecisenfast, and accuratejinformation. In the effectivenesslsector, the developmentlof information and communicationltechnology hasfgiven birth to E-Government.kHowever, thisssystem hassnot fully runnaccording to the government's expectations as stated in the Presidential Instruction (Inpres) No. 3 of 2003 concerning National E-Government Development Policies and Strategies. From the results of the study, it can be said that the effectiveness of E-Government at the Aceh Jaya HighsCourt insusing informationtto achievetwork results efficientlylhas notibeen fully implemented according to the government's expectations. In the effectiveness of E-Government there are still many problems that need to be resolved to facilitate the implementation of further effectiveness